Associação entre exposição à violência interpessoal e isolamento social com a adoção de práticas não saudáveis em relação ao peso - Okada, Letícia Martins (2018)
Introduction: Exposure to interpersonal violence and social isolation are common in adolescence and may be associated with unhealthy weight control practices. However, there is a lack of studies that identify joint associations between different forms of violence and social isolation with unhealthy weight control practices, in both sexes. Objective: To describe the prevalence of interpersonal violence (family physical violence, bullying), social isolation and unhealthy weight control practices in Brazilian adolescents, according to gender; To evaluate the association between interpersonal violence (family physical violence, bullying), social isolation and unhealthy weight control practices. Methods: We used data from the National School Health Survey (2015), with a representative sample of 9th grade students from public and private schools. The exposures were interpersonal violence (family physical violence, bullying based on body appearance and other reasons) suffered during the last month of the study, and social isolation; the outcomes were unhealthy weight control practices, such as self-induced vomiting/taking laxatives, taking any diet pills, powders, or liquids to lose or gaining weight/muscle mass without a doctor’s advice. We performed simple and multiple logistic regression models, stratified by sex and adjusted for confounding variables, to obtain the odds ratios (OR). Results: A little more than half of the adolescents were female (51.3%), the majority of them were aged between 11 and 15 years (89%), with a self-declared Brown color (43%) or White (36.1%) and children of mothers with incomplete middle education (33.9%) and complete high school (30.9%). The girls had higher prevalence of family physical violence (15.1%), bullying based on body appearance (7.8%), social isolation (28.7%) and induction of vomiting/laxative use (7.5%); while bullying for other reasons (39.9%) and use of any diet pills, powders, or liquids for loss (6.8%) and weight gain/muscle mass (8.6%) were more frequent among boys. All exposures were associated with greater adoption of unhealthy weight control practices. Girls who were victims of bullying based on body appearance were more likely to induce vomiting/take laxatives (OR2,29 95%CI 1,87-2,81), to take any diet pills, powders, or liquids for loss (OR1,92 95%CI 1,50-2,46) and gain of weight/muscle mass (OR1,51 95%CI 1,17-1,93), being this association stronger than with bullying for other reasons. Boys victims of family physical violence were almost twice as likely to adopt unhealthy practices, compared to girls. Conclusion: Interpersonal violence (family physical violence and bullying), as well as social isolation, were associated with unhealthy weight control practices among Brazilian adolescents.